Effect of e-health intervention on disease management in patients with chronic heart failure: A meta-analysis - Ding, Xueying; Wen, Yating; Tian, Zimeng; Wen, Yaru; Sun, Guokun; Geng, Rongxing; Fang, Wei; Xu, Yun (Frontiers in Cardiovascular Medicine, 2023)
Abstract: Objective The aim of this meta-analysis was to assess the impact of e-health interventions on disease management in patients with CHF. Methods Six databases including Embase, Web of Science, Scopus, PubMed, Cochrane, and EBSCO were searched by computer. The search time is before May 1, 2022. Odds ratios (OR) were used for binary categorical data and weighted mean differences (WMD) for continuous variables. The 95% confidence intervals (CI) were used to express the effect sizes for both count and measurement data. RevMan 5.4 and Stata 16.0 were employed to complete this meta-analysis. Results The study included 22 research studies and 5149 patients. E-health intervention can effectively reduce all-cause mortality [OR = 0.801, 95%CI:(0.650, 0.987), P < 0.05], all-cause hospitalization rate [OR = 0.66, 95%CI:(0.46, 0.95), P < 0.05] and heart failure related hospitalization rate [OR = 0.750, 95%CI:(0.632, 0.891), P < 0.05]. E-health intervention is also effective in improving the quality of life [WMD = 2.97, 95%CI:(1.54, 4.40), P < 0.05] and the self-management ability of patients [WMD = -2.76, 95%CI:(-5.52, -0.11), P < 0.05]. Conclusion E-health interventions can reduce all-cause mortality, all-cause hospitalization, and heart failure-related hospitalization in patients with CHF. Furthermore, it can improve the health-related quality of life of patients.